(untitled) (Marketing Journal, 2025)
This article examines the impact of corporate governance mechanisms on the sustainability and innovative development of transport companies in the Republic of Uzbekistan. Based on an analysis of regulatory documents, annual reports, and Agency for Developm ent of the Capital Market and Corporate Governance of the Republic of № 1 254 Uzbekistan (ARRUKR) data for 2020 –2024, the level of governance maturity in railway, aviation, and road transport organizations is assessed. Quantitative indicators of board independence, the dynamics of ESG reporting implementation, and innovation activit y are presented. Three case studies, a SWOT analysis, and comparisons with practices in South Korea (Korail), Germany (Deutsche Bahn), and France (SNCF) are conducted. Two research hypotheses are formulated and empirically validated, and practical recommen dations for institutional improvement of corporate governance are proposed.